• Reflections on the Relations between Organs in an Unwritten Constitution: The Case of Republican Rome - Petrucci, Aldo (2007)
In the history and constitutional evolution of republican Rome there are two crucial phenomena that contributed to its complex formation. Thus, the author points out that these key elements are: (i) the colonization or subjugation of defeated territories; and (ii) the triumphal ceremony, which involved the control of the supreme magistrates by the senate and the popular assembly. According to the author, these elements had an impact on the emergence and strengthening of rules through the practice of government and the relationship between constitutional bodies. To that extent, this work constitutes a relevant contribution to the study of republican Rome, as well as the analysis of political and juridical relations in antiquity.